Successful Treatment of Long-Term Severe Progressive Interstitial Pneumonia with Low-Dose Corticosteroid and Azathioprine in a Patient with Diffuse Systemic Sclerosis - Takuya Kotani; Tohru Takeuchi; Shigeki Makino; Toshiaki Hanafusa (Case Reports in Rheumatology)
For progressive interstitial pneumonia (progressive IP) that accompanies diffuse systemic sclerosis (diffuse SSc), no treatment guidelines have yet been established, and it is a complication with a poor prognosis. We herein report a case in which combination therapy of a low-dose corticosteroid and low-dose azathioprine was performed for progressive SSc-IP in a 64-year-old female whose respiratory function was severely damaged for a long period of time and for whom improvement was achieved. The beneficial effect has continued for 3 years with no side effects being observed during the course.